Preparation method of multifunctional conductive gel based on metal acid salt ionic liquid

By introducing zwitterionic structures into metallic acid ionic liquids, the construction of conductive gels is solved, and the problems of freezing and moisture failure of traditional hydrogels at low temperatures are achieved, and a high-performance conductive gel is suitable for flexible electronic devices.

CN119390891AActive Publication Date: 2025-02-07HUAZHONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411652126.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-07
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Traditional hydrogels freeze at low temperatures, resulting in reduced flexibility and conductivity and loss of large amounts of water at room temperature, limiting their long-term stability and operating durability.

Method used

By introducing zwitterionic structures into metallic acid ionic liquids containing unsaturated double bonds, a conductive gel based on metallic acid ionic liquid is constructed, and a covalent/non-covalent crosslinking network is formed using radical polymerization and crosslinking reactions.

Benefits of technology

The obtained hydrogel has good conductivity, flexibility, frost resistance and water retention properties. It is suitable for flexible wearable electronic devices, has multifunctional characteristics, and is simple in preparation, green and environmentally friendly, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390891A_ABST
    Figure CN119390891A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite gel materials, and discloses a preparation method of multifunctional conductive gel based on metal acid salt ionic liquid, which comprises the following steps: (1) uniformly dissolving metal halide in ionic liquid containing unsaturated double bonds, and uniformly stirring and mixing to obtain the metal acid salt ionic liquid; (2) jointly dissolving the zwitterionic raw material, a cross-linking agent and a metal acid salt ionic liquid in deionized water, and uniformly dispersing to obtain a mixed system; and (3) carrying out free radical polymerization reaction and cross-linking reaction on the mixed system to obtain the conductive gel based on the metal acid salt ionic liquid. The conductive gel based on the metal acid salt ionic liquid is jointly constructed by utilizing a zwitterionic structure under the participation of the metal acid salt ionic liquid containing unsaturated double bonds, and the obtained hydrogel has conductivity, flexibility, freezing resistance and water retention performance and has a huge application prospect in the field of flexible wearable electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite gel materials, and more specifically, relates to a method for preparing a multifunctional conductive gel based on metal salt ion liquid. Background Art

[0002] Hydrogels are soft materials composed of a three-dimensional cross-linked network and a large amount of water. Due to their high flexibility, structural designability and good biocompatibility, hydrogels are widely used as functional smart materials in fields such as wearable electronic devices. However, traditional hydrogels will inevitably freeze at low temperatures, and their flexibility and conductivity will be significantly reduced, which seriously affects their application in extreme environments (they often freeze at the freezing point of water and lose flexibility and cannot be used in the field of sensing). Even at room temperature, hydrogels will lose a lot of water in a few hours (for example, see: X. Sui, H. Guo, C. Cai, Q. Li, C. Wen, X. Zhang, X. Wang, J. Yang, L. Zhang, Ionic conductive hydrogels with long-lasting antifreezing, water retention and self-regeneration abilities, Chemical Engineering Journal 419 (2021) 129478.), which limits their long-term stability and operational durability. Therefore, it is very necessary to develop hydrogels with excellent antifreezing and water retention.

[0003] Monomer compounds or polymers with zwitterionic structures, wherein the zwitterionic structure is a dipole ion with both positive and negative charges on the same molecule, zwitterionic hydrogels have attracted much attention in the field of flexible electronic devices due to their unique structure, excellent antifreeze properties, water retention, conductivity, adhesion and biocompatibility. However, zwitterionic hydrogels have a strong affinity for water, which leads to poor mechanical properties (see: H. Wang, B. Liu, D. Chen, Z. Wang, H. Wang, S. Bao, P. Zhang, J. Yang, W. Liu, Low hysteresis zwitterionic supramolecular polymer ion-conductive elastomers with anti-freezing properties, high stretchability, and self-adhesion for flexible electronic devices, Materials Horizons 11 (11) (2024) 2628-2642.). In addition, the single network and toughening mechanism of zwitterionic hydrogels make them low in elasticity and poor in responsiveness to various deformations (see: Y.Liu, Q.Liu, L.Zhong, C.Chen, Z.Xu, Tough, antifreezing, and conductive double network zwitterionic-based hydrogel for flexible sensors, Chemical Engineering Journal 452 (2023) 139314.), which greatly limits their practical applications. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for preparing a multifunctional conductive gel based on a metal acid salt ionic liquid, wherein the specific composition of the conductive gel and the corresponding preparation method are improved, and the zwitterionic structure is used to jointly construct a conductive gel based on a metal acid salt ionic liquid with the participation of a metal acid salt ionic liquid containing an unsaturated double bond, and the obtained hydrogel has good conductivity, good flexibility, excellent antifreeze and water retention properties, excellent performance, great application prospects in the field of flexible wearable electronic devices, and has multifunctional characteristics. The method of the present invention is simple and effective, the reaction conditions are mild, the operation is simple, and it is suitable for industrial production.

[0005] To achieve the above object, according to one aspect of the present invention, a method for preparing a conductive gel based on a metal salt ionic liquid is provided, comprising the following steps:

[0006] (1) uniformly dissolving a metal halide in an ionic liquid containing an unsaturated double bond, and stirring and mixing the mixture to obtain a metal acid salt ionic liquid containing an unsaturated double bond;

[0007] (2) using a monomer compound and / or a polymer having a zwitterionic structure as a zwitterionic raw material, dissolving the zwitterionic raw material, a crosslinking agent, and the metal acid salt ionic liquid containing an unsaturated double bond in deionized water and dispersing them uniformly to obtain a mixed system;

[0008] (3) The mixed system is subjected to free radical polymerization and cross-linking reactions to obtain a conductive gel based on metal salt ionic liquid.

[0009] As a further preferred embodiment of the present invention, in step (2), the molar ratio of the metal acid salt ionic liquid containing unsaturated double bonds to the zwitterionic structure contained in the zwitterionic raw material is (0.01-2):1, preferably (0.1-1):1.

[0010] As a further preferred embodiment of the present invention, in step (1), the molar ratio of the ionic liquid containing unsaturated double bonds to the metal halide is (0.01-20):1, preferably (0.5-10):1.

[0011] As a further preferred embodiment of the present invention, in step (1), the metal element in the metal halide is one or more of Zn, Zr, Al, Ga, In, Fe, and Cu, and the halogen is one or more of F, Cl, Br, and I;

[0012] The anion of the ionic liquid containing an unsaturated double bond is one or more of F, Cl, Br, and I;

[0013] The ionic liquid containing unsaturated double bonds is at least one of an imidazolium salt ionic liquid containing unsaturated double bonds, a quaternary ammonium salt ionic liquid containing unsaturated double bonds, a pyridinium salt ionic liquid containing unsaturated double bonds, and a quaternary phosphonium salt ionic liquid containing unsaturated double bonds;

[0014] Preferably, the ionic liquid containing an unsaturated double bond is an imidazolium salt ionic liquid containing an unsaturated double bond, and the length of the alkyl carbon chain is 1 to 12 carbon atoms.

[0015] As a further preferred embodiment of the present invention, in step (2), the monomer compound having a zwitterionic structure is preferably betaine or a derivative thereof;

[0016] The concentration of the cross-linking agent in the mixed system is 0.001M to 0.5M;

[0017] The cross-linking agent is preferably N,N-methylenebisacrylamide.

[0018] As a further preferred embodiment of the present invention, in step (1), the stirring and mixing is performed at 20 to 80° C. for 2 to 12 hours;

[0019] In step (2), the uniform dispersion is specifically achieved by ultrasonic dispersion.

[0020] As a further preferred embodiment of the present invention, in step (3), the free radical polymerization reaction and the cross-linking reaction are preferably induced by ionizing radiation treatment;

[0021] The ionizing radiation treatment is specifically irradiation treatment using any one of electron beams, gamma rays or X-rays; the absorbed dose of the ionizing radiation is 1 to 200 KGy, preferably 10 to 50 KGy.

[0022] According to another aspect of the present invention, the present invention provides a conductive gel based on metal acid salt ionic liquid obtained by the above preparation method.

[0023] According to another aspect of the present invention, the present invention provides the use of the above-mentioned conductive gel based on metal salt ionic liquid as a sensing material in a flexible strain sensor.

[0024] As a further preferred embodiment of the present invention, the flexible strain sensor is a wearable device, which senses strain by utilizing changes in resistance and / or conductivity of a conductive gel based on a metal salt ionic liquid;

[0025] Preferably, the ambient temperature of the application is above -60°C.

[0026] Through the above technical scheme conceived by the present invention, compared with the prior art, in the present invention, the metal acid salt ionic liquid containing unsaturated double bonds is a functional ionic liquid composed of anionic groups formed by complexation of organic cations and metal ions with halogen ions. The metal acid salt ionic liquid containing unsaturated double bonds combines the unique properties of ionic liquids and metal ions, interacts with zwitterionic structures through abundant reversible bonds (hydrogen bonds, coordination bonds, etc.), effectively disperses stress and dissipates energy, and improves the mechanical strength and elasticity of the gel. The obtained hydrogel has multifunctional characteristics such as good electrical conductivity, good flexibility, excellent antifreeze and water retention properties, and can be particularly applied to the field of flexible electronics.

[0027] Specifically, the present invention can achieve the following beneficial effects:

[0028] (1) The present invention utilizes zwitterionic structures to construct a conductive gel based on metal salt ionic liquids with the participation of metal salt ionic liquids containing unsaturated double bonds. The obtained hydrogel has good conductivity, good flexibility, excellent antifreeze and water retention properties, excellent performance, great application prospects in the field of flexible wearable electronic devices, and multifunctional characteristics. In addition, the preparation method can especially use ionizing radiation technology to induce free radical polymerization and crosslinking reactions. The preparation method involved has the advantages of being able to be carried out at room temperature, not requiring an initiator, being green and environmentally friendly, and being able to be mass-produced industrially.

[0029] (2) The synergistic effects of covalent and multiple non-covalent interactions endow the hydrogel with excellent mechanical tensile properties, high compressive strength, ultrafast response time, water retention and antifreeze properties. Based on its excellent properties, the conductive hydrogel is used as a multifunctional flexible sensor to reliably and timely detect large-scale and small movements of the human body. As shown in the examples below, Morse code information can also be transmitted through finger movements.

[0030] (3) The multifunctional conductive hydrogel prepared by the present invention has broad application prospects in the fields of wearable devices, electronic skin and encrypted transmission of intelligent information.

[0031] Considering that coordination bonds have higher bond energy and a wider binding strength spectrum, their controllable structure is crucial for hydrogels. Previous studies on the synthesis of metal coordination complexes involved the use of organic solvents and complicated processes (see: X. Guan, Y. Zhu, B. Zhang, X. Sun, MA Abosheasha, C. Gong, S. Zheng, D. Li, Q. Han, M. An, M. Ueda, Y. Ito, Shutters-Inspired metal ions coordination hydrogel Strain / Pressure sensor for joint behavior evaluation and flatfeet correction, Chemical Engineering Journal 489 (2024) 151353.), while the present invention innovatively introduces metal halides into ionic liquids containing unsaturated double bonds through a simple method to form metal acid salt ionic liquids, and establishes a covalent / non-covalent cross-linking network with zwitterions through free radical polymerization to form a conductive gel. Furthermore, most of the metal salt ionic liquids reported in the prior art are used as solvents, while the present invention uses metal salt ionic liquids containing unsaturated double bonds, which not only provide a large number of coordination sites, but also form polyionic liquid chains through free radical polymerization. In the gel formation process, the formed polyionic liquid chain segments are more likely to strengthen the gel through non-covalent interaction and entanglement with zwitterionic chain segments. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The synthesized metal salt ionic liquid [ABIm][Zn x Cl y ](3:1).

[0033] Figure 2 [ABIm]Cl, anhydrous ZnCl2, [ABIm][Zn x Cl y ](1:1) and [ABIm][Zn x Cl y ](3:1)'s infrared spectrum.

[0034] Figure 3 The stability test results of the PI6Z6 hydrogel in Example 1; wherein, Figure 3 a in the figure is the differential scanning calorimetry graph of the PI6Z6 hydrogel in Example 1; Figure 3 b in the figure is the change in weight retention rate of the PI6Z6 hydrogel in Example 1 when placed in an open environment at room temperature.

[0035] Figure 4 The mechanical stretching curves of the hydrogels prepared in Example 1 and Example 3.

[0036] Figure 5 This is the mechanical stretching curve of the hydrogel prepared in Example 4.

[0037] Figure 6 This is the mechanical stretching curve of the hydrogel prepared in Comparative Example 2.

[0038] Figure 7 This is the compression curve of the PI6Z6 hydrogel in Example 1.

[0039] Figure 8 Response and recovery time of PI6Z6 hydrogel during stretching in Example 1.

[0040] Fig. 9 is the signal response curve of the PI6Z6 hydrogel in Example 1 to different human body movements. Fig. 9 a in the figure represents the bending of the finger (PI6Z6 hydrogel is located at the finger at this time). Fig. 9 b in the figure represents wrist bending (PI6Z6 hydrogel is located at the wrist at this time). Fig. 9 Figure c shows a volunteer coughing (at this time the PI6Z6 hydrogel is located in the throat).

[0041] Fig.10 This is an example of the application of the PI6Z6 hydrogel prepared in Example 1 in information encryption transmission; wherein, Fig.10 The a in is the Morse code table, Fig.10 b and Fig.10 c in the figure is the response signal of PI6Z6 hydrogel to "HUST" and "HELP" according to the Morse code table. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0043] The present invention first prepares a metal acid salt ionic liquid. The following examples use a metal acid salt ionic liquid prepared by the following preparation method using commercially available raw materials as raw materials.

[0044] 1-allyl-3-butylimidazolium chloride ([ABIm]Cl) and anhydrous ZnCl2 were stirred at 50 °C for 8 h to synthesize the metal salt ionic liquid ([ABIm][Zn x Cly ]), a clear and homogeneous solution was obtained, such as Figure 1 As shown. According to the molar ratio of [ABIm]Cl to anhydrous ZnCl2 of 3:1 and 1:1 respectively, the prepared metal salt ionic liquids are named [ABIm][Zn x Cl y ](3:1),[ABIm][Zn x Cl y ](1:1). As a supplementary explanation: [ABIm][Zn x Cl y The molar mass of [ABIm][ZnCl2](3:1) is calculated by (3*molar mass of [ABIm]Cl+molar mass of ZnCl2) / 4; x Cl y The molar mass of ](1:1) is calculated by (molar mass of [ABIm]Cl + molar mass of ZnCl2) / 2.

[0045] Example 1

[0046] Prepare a mixed system in which [ABIm][Zn x Cl y ](3:1) with a molar concentration of 6 M, sulfobetaine methacrylate (SBMA) with a molar concentration of 6 M, and N,N-methylenebisacrylamide with a molar concentration of 0.012 M (the mixed system is specifically composed of [ABIm][Zn x Cl y ](3:1), SBMA and N,N-methylenebisacrylamide are dissolved in 2 ml of deionized water and ultrasonically dispersed uniformly), and then the mixed system is irradiated under electron beam to obtain PI6Z6 hydrogel. The absorbed dose of electron beam irradiation is 20KGy.

[0047] Example 2

[0048] This example uses the same method as in Example 1 to prepare a multifunctional conductive hydrogel, except that the concentration of SBMA is 5 M, and the synthesized gel is named PI6Z5 hydrogel.

[0049] Example 3

[0050] This example uses the same method as in Example 1 to prepare a multifunctional conductive hydrogel, except that the concentration of SBMA is 7 M, and the synthesized gel is named PI6Z7 hydrogel.

[0051] Example 4

[0052] Prepare a mixed system in which [ABIm][Zn x Cly ](1:1) with a molar concentration of 6 M, sulfobetaine methacrylate (SBMA) with a molar concentration of 6 M, and N,N-methylenebisacrylamide with a molar concentration of 0.012 M (the mixed system is specifically composed of [ABIm][Zn x Cl y ](1:1), SBMA and N,N-methylenebisacrylamide are dissolved in 2 ml of deionized water and dispersed uniformly by ultrasonication, and then the mixed system is irradiated under electron beam to obtain PI6Z6(1:1) hydrogel. The absorbed dose of electron beam irradiation is 20KGy.

[0053] Comparative Example 1

[0054] A mixed system is prepared, in which the molar concentration of [ABIm]Cl is 6M, the molar concentration of sulfobetaine methacrylate (SBMA) is 6M, and the molar concentration of N,N-methylenebisacrylamide is 0.012M (the mixed system is specifically obtained by dissolving [ABIm]Cl, SBMA and N,N-methylenebisacrylamide in 2 ml of deionized water and uniformly dispersing them by ultrasonication), and then the mixed system is irradiated under an electron beam, wherein the absorbed dose of the electron beam irradiation is 20KGy.

[0055] Comparative Example 2

[0056] A mixed system is prepared, in which the molar concentration of [ABIm]Cl is 4.5M, the molar concentration of anhydrous ZnCl2 powder is 1.5M, the molar concentration of sulfobetaine methacrylate (SBMA) is 6M, and the molar concentration of N,N-methylenebisacrylamide is 0.012M (the mixed system is specifically obtained by dissolving [ABIm]Cl, anhydrous ZnCl2, SBMA and N,N-methylenebisacrylamide in 2ml of deionized water and uniformly dispersing them by ultrasonication), and then the mixed system is irradiated under an electron beam, wherein the absorbed dose of the electron beam irradiation is 20KGy.

[0057] Performance testing:

[0058] The synthesized metal salt ionic liquid was tested by Fourier transform infrared (FTIR), such as Figure 2 Compared with pure [ABIm]Cl, when the molar concentration ratio of [ABIm]Cl to ZnCl2 is 3:1, 3049cm -1 (=CH stretching vibration) and 3136cm -1 The peak at (CH stretching vibration) moves to a higher wave number (3072 cm -1 and 3142cm -1) shift. When the molar concentration ratio of [ABIm]Cl to ZnCl2 is changed to 1:1, [ABIm][Zn x Cl y The stretching peak of ](1:1) shifts to a higher wave number. The above results prove the successful synthesis of metal salt ionic liquids and indicate that the addition of metal halides weakens the effect of halide ions on imidazolium cations.

[0059] The conductivity of the PI6Z6 hydrogel obtained in Example 1 was tested. The results showed that the conductivity of the PI6Z6 hydrogel at room temperature was 1.36 mS cm -1 , and it is also conductive at -60℃.

[0060] In terms of stability, differential scanning calorimetry (DSC) further proved that the PI6Z6 hydrogel in Example 1 had good antifreeze properties (phase transition temperature: -70.6°C). Figure 3 In addition, after being placed in an open environment at room temperature for 30 days, the PI6Z6 hydrogel can still maintain 86.4% of its original weight, as shown in Fig. Figure 3 As shown in b.

[0061] Figure 4 The mechanical properties of the hydrogels prepared in Example 1 and Example 3 are compared. The results show that no matter the SBMA concentration is 6M or 7M, the obtained hydrogels have good mechanical properties (of course, the PI6Z6 hydrogel obtained in Example 1 has the best comprehensive strength and strain properties).

[0062] Figure 5 The mechanical properties of the hydrogel prepared in Example 4 are shown. Compared with the PI6Z6 hydrogel prepared in Example 1, the strain of the PI6Z6 (1:1) hydrogel prepared in Example 4 is reduced and the stress is increased, and it also has good mechanical properties.

[0063] The hydrogel obtained in Comparative Example 1 is very soft and has low stress, so it is difficult to remove the complete shape for subsequent mechanical testing. The strength of the gel prepared in Comparative Example 2 is improved by adding ZnCl2 powder, but it is still very weak. Figure 6As shown, the strength of the obtained gel (10kPa) is much lower than the strength of the PI6Z6 hydrogel (57kPa) prepared in Example 1. This result further confirms the important role of metal salt ionic liquids, which can enhance SMBA hydrogels. That is, the hydrogel obtained by modifying sulfobetaine methacrylate (SBMA) with common ionic liquid 1-allyl-3-butyl imidazole chloride ([ABIm]Cl) is very soft and has low stress, so it is difficult to take out the complete shape for subsequent mechanical testing; adding ZnCl2 powder to the above system improves the strength of the gel, but it is still very weak, and the strength of the obtained gel (10kPa) is much lower than the strength of the PI6Z6 hydrogel (57kPa) prepared with metal salt ionic liquids; these results confirm that metal salt ionic liquids can enhance zwitterionic hydrogels.

[0064] The PI6Z6 hydrogel prepared in Example 1 has good compressive resistance. Figure 7 As shown, the compressive strength of the obtained hydrogel is as high as 820 kPa at 90% strain.

[0065] The PI6Z6 hydrogel prepared in Example 1 was deformed using a stretching machine. The deformation was applied at 0.14s and maintained until it was removed at 1.34s. The change in resistance was as follows: Figure 8 As shown, it can be seen that the response and recovery time of the PI6Z6 hydrogel prepared in Example 1 is 0.14 s, which indicates that it can sensitively sense external stimuli and quickly provide corresponding real-time electrical signals.

[0066] The PI6Z6 hydrogel sensor prepared in Example 1 can quickly and accurately detect the movement of fingers at different bending angles ( Fig. 9 a). Fig. 9 As shown in Figure b, the hydrogel sensor can also be attached to the wrist to monitor the movement of the wrist in real time during bending by collecting electrical signals. In addition, the hydrogel sensor attached to the throat can also accurately detect the repetitive signals of the volunteer's cough ( Fig. 9 c) in.

[0067] The hydrogel sensors can be used to transmit information in real time via Morse code, an efficient real-time coding system that uses a series of dots and dashes to represent letters of the English alphabet, such as Fig.10 The PI6Z6 hydrogel prepared in Example 1 was glued to the finger, and the bending and holding time of the finger were controlled to generate spikes and platform peaks, and the corresponding electrical signals such as "HUST" and "HELP" were detected and transmitted in real time ( Fig.10 b in Fig.10 (as shown in c in the figure).

[0068] The above embodiments are only examples. For example, the metal element in the metal salt ionic liquid may be one or more of Zn, Zr, Al, Ga, In, Fe, and Cu, and the halogen in the anion group in the metal salt ionic liquid may be one or more of F, Cl, Br, and I. For another example, in addition to ionizing radiation induction, free radical polymerization may also be induced by other methods known in the prior art, such as light initiation and thermal initiation.

[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a conductive gel based on metal salt ionic liquid, characterized in that: The following steps are involved: (1) uniformly dissolving a metal halide in an ionic liquid containing an unsaturated double bond, and stirring and mixing the mixture to obtain a metal acid salt ionic liquid containing an unsaturated double bond; (2) using a monomer compound and / or a polymer having a zwitterionic structure as a zwitterionic raw material, dissolving the zwitterionic raw material, a crosslinking agent, and the metal acid salt ionic liquid containing an unsaturated double bond in deionized water and dispersing them uniformly to obtain a mixed system; (3) The mixed system is subjected to free radical polymerization and cross-linking reactions to obtain a conductive gel based on metal salt ionic liquid.

2. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of the metal acid salt ionic liquid containing unsaturated double bonds to the zwitterionic structure contained in the zwitterionic raw material is (0.01-2):1, preferably (0.1-1):

1.

3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the ionic liquid containing unsaturated double bonds to the metal halide is (0.01-20):1, preferably (0.5-10):

1.

4. The preparation method according to claim 1, characterized in that: In step (1), the metal element in the metal halide is one or more of Zn, Zr, Al, Ga, In, Fe, and Cu, and the halogen is one or more of F, Cl, Br, and I; The anion of the ionic liquid containing an unsaturated double bond is one or more of F, Cl, Br, and I; The ionic liquid containing unsaturated double bonds is at least one of an imidazolium salt ionic liquid containing unsaturated double bonds, a quaternary ammonium salt ionic liquid containing unsaturated double bonds, a pyridinium salt ionic liquid containing unsaturated double bonds, and a quaternary phosphonium salt ionic liquid containing unsaturated double bonds; Preferably, the ionic liquid containing an unsaturated double bond is an imidazolium salt ionic liquid containing an unsaturated double bond, and the length of the alkyl carbon chain is 1 to 12 carbon atoms.

5. The preparation method according to claim 1, characterized in that: In step (2), the monomer compound having a zwitterionic structure is preferably betaine or a derivative thereof; The concentration of the cross-linking agent in the mixed system is 0.001M to 0.5M; The cross-linking agent is preferably N,N-methylenebisacrylamide.

6. The preparation method according to claim 1, characterized in that: In step (1), the stirring and mixing is performed at 20 to 80° C. for 2 to 12 hours; In step (2), the uniform dispersion is specifically achieved by ultrasonic dispersion.

7. The preparation method according to claim 1, characterized in that: In step (3), the free radical polymerization reaction and the cross-linking reaction are preferably induced by ionizing radiation treatment; The ionizing radiation treatment is specifically irradiation treatment using any one of electron beams, gamma rays or X-rays; the absorbed dose of the ionizing radiation is 1 to 200 KGy, preferably 10 to 50 KGy.

8. A conductive gel based on metal salt ionic liquid obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the conductive gel based on metal salt ionic liquid as claimed in claim 8 as a sensing material in a flexible strain sensor.

10. The use according to claim 9, characterized in that The flexible strain sensor is a wearable device that senses strain by utilizing changes in resistance and / or conductivity of a conductive gel based on a metal salt ionic liquid; Preferably, the ambient temperature of the application is above -60°C.

Citation Information

Patent Citations

  • Synthesis and application of high performance and high strength composite gel with loaded gold nano particles

    CN108404980A

  • Antibacterial / lubricating dual-function coating as well as preparation method and application thereof

    CN118320182A